Energy efficient cluster head selection for cross layer design over wireless sensor network. (2016) - Chaturvedi, Anshu; Goswami, D.N.; Singh, Shivjay
Wireless sensor network energy efficiency acquired attraction of the research community. In WSN, nodes deploy in sensor environment and communicate with other nodes with the help of cluster node. Here cluster node directly connected through base station. Due to very small equipments, sensor devices have very less power capacity and it affects the overall performance of networks. Energy is one of the most important issues that have been accepted by the research community to obtain the network scalability, stability and increase performance of the sensor network. While data transmission nodes deduct their energy, and this is most difficult to select effective cluster head when node have less energy. In this paper we proposed an algorithm for selection cluster head in minimum energy over cross layer. We simulate our algorithm over LEACH routing protocol, which has been acquired for their energy efficiency and easiness. The objective of this paper is to provide optimised selection procedure for cluster head node bashed on node energy to increase the life time of a sensor network, which increase the total performance of the network.